Novel acquisition strategies for dissolution dynamic nuclear polarisation - McGeorge-Henderson, Ben P. (2017)
Dynamic Nuclear Polarisation (DNP) produced molecules with spin polarisation levels that are up to three orders of magnitude larger than their thermal equilibrium values. Most DNP mechanisms work at temperatures of 2 K and lower, meaning that the sample is stored in the solid-state. Combining DNP with a rapid temper- ature jump to room temperature allows liquid-state NMR analysis with a signal that is ve orders of magnitude higher than observed with thermal polarisation. However, the information obtained during a dissolution experiment is limited by the intrinsic liquid-state longitudinal relaxation of the spins of interest. is thesis looks to increase the information acquired in a number of ways. First, by devel- oping a new dissolution system for the dual iso-centre magnet it was possible to reproducibly perform enhanced NMR acquisition 600 ms following sample disso- lution. is has allowed the observation of hyperpolarised 13C spins with T1 times as low as 200 ms. Complimentary information can be obtained following sample dissolution by observing multiple spin species simultaneously. 13C and 15N spins are both polarised by microwave irradiation of the same frequency, so both can be analysed during a single dissolution DNP experiment. A novel probe has been used that contains six individual 13C microcoils. ese coils are separated in space and operate independently. is probe, in conjunction with dissolution DNP, can be used for observing dynamic molecular information on the time scale of 200 ms, however with further development this time scale should drop to less than 100 ms while maintaining a required minimum spectral resolution. Initial tests have been performed with both thermally polarised and hyperpolarised samples.